Effect of Chemical Properties of Milk Thistle Seed Oil on Serum Lipid Profile and Antioxidants Capacity in Rats Fed High Cholesterol and Cholesterol Free Diets - Dabbour, I.R.; Ahmad, M.N.; Takruri, H.R.; Al-Ismail, K.M. (Pakistan Journal of Nutrition, 2014)
This study aimed to examine the in vivo effect of chemical properties of cold-pressed Milk Thistle Seed Oil (MTSO) on serum lipid profile, lipid peroxidation product (MDA) and total antioxidant capacity (TAC).These examinations were carried out to investigate the long-term effect of feeding two levels of MTSO in experimental diets with and without cholesterol. Sixty-four adult male Sprague-Dawley rats were divided into eight groups. Four groups were on free cholesterol diets with either 4% MTSO, 8% MTSO, 4% control (soybean oil) or 8% control oil. The other 4 groups were fed 1% cholesterol with percentages of oils similar to the first four groups for 12 weeks. Regarding serum lipoproteins there were significant differences (p<0.05) in TC in 8% MTSO and 8% control cholesterol-supplemented diets when compared with 8%control cholesterol-free diets. Also LDL-C of cholesterol-supplemented diet groups were significantly higher (p<0.05) than cholesterol-free diet groups. An interesting result was the significantly high levels (p<0.05) of HDL-C in rats fed cholesterol-free diet with MTSO 4 and 8% when compared to cholesterol-supplemented diets. There was a significantly higher (p<0.05) HDL-C/LDL-C ratio for cholesterol-free diets than cholesterol-supplemented diets. Subsequently, high significant difference (p<0.05) was observed in AI values at 8% cholesterol-supplemented diet when compared with cholesterol-free diet. MDA showed clearly high levels at 8% control oil with or without cholesterol. Regarding the TAC, it was higher (p<0.05) in 4% cholesterol-free MTSO diet when compared to 8% cholesterol-free control diet and 4% cholesterol supplemented MTSO diet. Based on the results obtained, the % of oil and presence of cholesterol were the main factors affecting the lipid profile, calculated AI, lipid peroxidation and TAC. With respect to in vivo lipid peroxidation, MTSO was clearly superior to soybean oil.